KESELAMATAN PASIEN DALAM PELAYANAN KESEHATAN PADA INSTALASI RAWAT INAP DI RUMAH SAKIT MULTAZAM MEDIKA BEKASI TAHUN 2013 - , Indra Narendra; , R.A. Antari Innaka T, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Provision of health services to patients in the inpatient care unit hospital has risk potentials of inciden to the safety patient. The number of the incidence tends to be high currently. The impact of health incidence to the patients safety is bad and could ultimately result in medical diputes. The occurance of health incidence reflects the lack of hospitals care to maintain the patientssafety. In such this condition, it is necessary to apply standards on patients safety optimally, to provide the legal protection to patients when they receive health services from hospital, and hospital should have internal policy related to patients safety treatment. This study is an empiricalâyudicial researcher, is a studythat is usedtoexamine theeffectiveness ofthe oflaw enforcementinsociety. This research was doneby combining both oflibrary researchandfield research. Library researchaimedatobtainingsecondary datawas done bythe studyingthe available documents. Field research was done to obtain primary data, and subject of research was determined usingnon-random samplingmethod, and thesamplewere determined bypurposivesample method. The primary data of the study obtained by interviewing and distributing questionairs to the respondent.The analysiswas done bydescriptivequalitative Basedon the results of this research,the implementation ofpatient safetyin MultazamMedikaHospitalshad been made, however in general the efforts were not optimally made yet. The forms oflegal protection forthe patientis obtainedfromthe laws regulating responbilities of hospitals toapplythe standardon patient safety, hospitalliabilityfor anylosssuffered byapatient, and thesanctioncould be given tothe hospitals when the violations of patients safety treatment occurs. Theinternalpoliciesrelated topatient safetyatMultazamMedikaHospitalwas documented in a Standard Operating Procedures (SOP) whichis usedas a guidence inproviding health servicestoavoidanincidentpatients safety.